Religions of Japan in practice - Tanabe, George J., Jr., 1943- (Princeton readings in religions., 1999)
This anthology reflects a range of Japanese religions in their complex, sometimes conflicting, diversity. In the tradition of the Princeton Readings in Religions series, the collection presents documents (legends and miracle tales, hagiographies, ritual prayers and ceremonies, sermons, reform treatises, doctrinal tracts, historical and ethnographic writings), most of which have been translated for the first time here, that serve to illuminate the mosaic of Japanese religions in practice. George Tanabe provides a lucid introduction to the "patterned confusion" of Japan's religious practices. He has ordered the anthology's forty-five readings under the categories of "Ethical Practices," "Ritual Practices," and "Institutional Practices," moving beyond the traditional classifications of chronology, religious traditions (Shinto, Confucianism, Buddhism, etc.), and sects, and illuminating the actual orientation of people who engage in religious practices. Within the anthology's three broad categories, subdivisions address the topics of social values, clerical and lay precepts, gods, spirits, rituals of realization, faith, court and emperor, sectarian founders, wizards, and heroes, orthopraxis and orthodoxy, and special places. Dating from the eighth through the twentieth centuries, the documents are revealed to be open to various and evolving interpretations, their meanings dependent not only on how they are placed in context but also on how individual researchers read them. Each text is preceded by an introductory explanation of the text's essence, written by its translator. Instructors and students will find these explications useful starting points for their encounters with the varied worlds of practice within which the texts interact with readers and changing contexts. Religions of Japan in Practice is a compendium of relationships between great minds and ordinary people, abstruse theories and mundane acts, natural and supernatural powers, altruism and self-interest, disappointment and hope, quiescence and war. It is an indispensable sourcebook for scholars, students, and general readers seeking engagement with the fertile "ordered disorder" of religious practice in Japan.